2022
DOI: 10.1002/2211-5463.13372
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal peptidases—intriguing roles in cancer progression and neurodegeneration

Abstract: Lysosomal peptidases are hydrolytic enzymes capable of digesting waste proteins that are targeted to lysosomes via endocytosis and autophagy. Besides intracellular protein catabolism, they play more specific roles in several other cellular processes and pathologies, either within lysosomes, upon secretion into the cell cytoplasm or extracellular space, or bound to the plasma membrane. In cancer, lysosomal peptidases are generally associated with disease progression, as they participate in crucial processes lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 381 publications
(517 reference statements)
0
10
0
Order By: Relevance
“…This issue contained five Review articles focussed on the important role of lysosomes, once thought to be little more than waste disposal units, in health and disease: in their article, Jonathan Martinez‐Fabregas, Irene Díaz‐Moreno and colleagues indicated that the lysosome is part of a complex communication network between organelles, and lysosome dysfunction is linked to a variety of pathologies [ 1 ]. These disease states include cancer and neurodegeneration, as reviewed by Janko Kos and co‐authors in the same issue [ 2 ]. Lysosomes are also implicated in ageing‐related diseases through cross‐talk between the autophagy‐lysosome pathway and mTORC1 activity; Timothy J. Sargeant and colleagues explored this interaction and whether targeting this pathway might slow the ageing process [ 3 ].…”
Section: New Developments In 2022mentioning
confidence: 99%
“…This issue contained five Review articles focussed on the important role of lysosomes, once thought to be little more than waste disposal units, in health and disease: in their article, Jonathan Martinez‐Fabregas, Irene Díaz‐Moreno and colleagues indicated that the lysosome is part of a complex communication network between organelles, and lysosome dysfunction is linked to a variety of pathologies [ 1 ]. These disease states include cancer and neurodegeneration, as reviewed by Janko Kos and co‐authors in the same issue [ 2 ]. Lysosomes are also implicated in ageing‐related diseases through cross‐talk between the autophagy‐lysosome pathway and mTORC1 activity; Timothy J. Sargeant and colleagues explored this interaction and whether targeting this pathway might slow the ageing process [ 3 ].…”
Section: New Developments In 2022mentioning
confidence: 99%
“… 55 In addition to their predominantly extracellular effects associated with cancer, intracellular proteolytic processes mediated by cysteine cathepsins have also been linked to tumor progression. 56 , 57 With regard to the particular function of cathepsin B in neoplastic diseases, the secretion of this cathepsin seems to be regulated by tumor-associated processes. Accordingly, the lower pH in the tumor microenvironment induces the relocation of cathepsin B-containing vesicles to the cell surface and the release of their content into the extracellular space.…”
Section: Introductionmentioning
confidence: 99%
“…Cleavage of the cell adhesion protein E-cadherin enhances metastasis . In addition to their predominantly extracellular effects associated with cancer, intracellular proteolytic processes mediated by cysteine cathepsins have also been linked to tumor progression. , With regard to the particular function of cathepsin B in neoplastic diseases, the secretion of this cathepsin seems to be regulated by tumor-associated processes. Accordingly, the lower pH in the tumor microenvironment induces the relocation of cathepsin B-containing vesicles to the cell surface and the release of their content into the extracellular space. , Additionally, the enzyme is secreted by tumor-associated benign cells such as macrophages, fibroblasts, osteoclasts, T-lymphocytes, and endothelial cells. , The correlation between cathepsin B activity and the metastatic potential in B16 melanoma cells was demonstrated 40 years ago …”
Section: Introductionmentioning
confidence: 99%
“…The cathepsins, members of the large family of papain-like cysteine peptidases, have become the subject of intense research because of their increasingly well-defined roles in immune responses, both in homeostatic conditions and in autoimmunity and the host response to tumors 1 , 2 . Of particular note is the role of the endosomal/lysosomal aminopeptidase cathepsin C (CatC) in coordinating activation of serine proteases released from azurophilic granules of stimulated neutrophils 1 3 . These proteases, which include neutrophil elastase, proteinase 3 (PR3), and neutrophil serine protease 4 (NSP4), are an important defense against bacterial infection and collateral tissue injury 1 , 2 .…”
mentioning
confidence: 99%
“…Of particular note is the role of the endosomal/lysosomal aminopeptidase cathepsin C (CatC) in coordinating activation of serine proteases released from azurophilic granules of stimulated neutrophils 1 3 . These proteases, which include neutrophil elastase, proteinase 3 (PR3), and neutrophil serine protease 4 (NSP4), are an important defense against bacterial infection and collateral tissue injury 1 , 2 . They are thought to be responsible for the hyperacute inflammation in the lung injury mediated by severe acute respiratory syndrome coronavirus 2 3 , 4 .…”
mentioning
confidence: 99%